2014
DOI: 10.2337/dc13-1852
|View full text |Cite
|
Sign up to set email alerts
|

Midregional Fragment of Proadrenomedullin, New-Onset Albuminuria, and Cardiovascular and All-Cause Mortality in Patients With Type 2 Diabetes (ZODIAC-30)

Abstract: OBJECTIVEThe midregional fragment of proadrenomedullin (MR-proADM) is a marker of endothelial dysfunction and has been associated with a variety of diseases. Our aim was to investigate whether MR-proADM is associated with new-onset albuminuria and cardiovascular (CV) and all-cause mortality in patients with type 2 diabetes treated in primary care. RESEARCH DESIGN AND METHODSPatients with type 2 diabetes participating in the observational Zwolle Outpatient Diabetes Project Integrating Available Care (ZODIAC) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Interestingly, although several previous studies have suggested that ProADM was also associated with other adverse outcomes in addition to all-cause mortality [26, 27, 3336, 4446], we did not find such statistically significant association with the incidence of our secondary combined endpoint including pulmonary embolism and MACCE. Also, in contrast to another study [39], our analysis did not find an association of ProADM with new onset diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, although several previous studies have suggested that ProADM was also associated with other adverse outcomes in addition to all-cause mortality [26, 27, 3336, 4446], we did not find such statistically significant association with the incidence of our secondary combined endpoint including pulmonary embolism and MACCE. Also, in contrast to another study [39], our analysis did not find an association of ProADM with new onset diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 98%
“…Higher plasma levels of ADM or of MR-proADM were observed in patients with diabetic nephropathy than in patients without nephropathy in small cross-sectional Japanese and Chinese studies (25,26). However, no independent association was observed with the incidence of new cases of albuminuria in a larger Dutch study (ZODIAC) with a median follow-up of 5.6 years (27). Association of high plasma MR-proADM with cardiovascular morbidity and mortality has also been reported in diabetic and nondiabetic subjects (21)(22)(23)(24)27).…”
Section: Discussionmentioning
confidence: 89%
“…However, no independent association was observed with the incidence of new cases of albuminuria in a larger Dutch study (ZODIAC) with a median follow-up of 5.6 years (27). Association of high plasma MR-proADM with cardiovascular morbidity and mortality has also been reported in diabetic and nondiabetic subjects (21)(22)(23)(24)27). Associations of rs2957692 and rs2957717 with plasma MRproADM have been reported in other populations (35,39).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We evaluated the effect of liraglutide on five biomarkers that are associated with cardiovascular disease in patients with diabetes: tumour necrosis factor (TNF)‐α, a pro‐inflammatory cytokine; soluble urokinase plasminogen‐activator‐receptor (suPAR), a marker of endothelial dysfunction and inflammation; mid‐regional pro‐adrenomedullin (MR‐proADM), a marker of systemic inflammation; mid‐regional pro‐atrial natriuretic peptide (MR‐proANP), a natriuretic peptide; and copeptin, a surrogate marker of arginine vasopressin …”
Section: Introductionmentioning
confidence: 99%